Tailored Single-Atom Collisions at Ultralow Energies - Schmidt, Felix; Mayer, Daniel; Bouton, Quentin; Adam, Daniel; Lausch, Tobias; Nettersheim, Jens; Tiemann, Eberhard; Widera, Artur (Physical Review Letters, 2019)
We employ collisions of individual atomic cesium (Cs) impurities with an ultracold rubidium (Rb) gas to probe atomic interaction with hyperfine- and Zeeman-state sensitivity. Controlling the Rb bath's internal state yields access to novel phenomena observed in interatomic spin exchange. These can be tailored at ultralow energies, owing to the excellent experimental control over all relevant energy scales. First, detecting spin-exchange dynamics in the Cs hyperfine-state manifold, we resolve a series of previously unreported Feshbach resonances at magnetic fields below 300 mG, separated by energies as low as h×15 kHz. The series originates from a coupling to molecular states with binding energies below h×1 kHz and wave function extensions in the micrometer range. Second, at magnetic fields below ≈100 mG, we observe the emergence of a new reaction path for alkali atoms, where in a single, direct collision between two atoms two quanta of angular momentum can be transferred. This path originates from the hyperfine analog of dipolar spin-spin relaxation. Our work yields control of subtle ultralow-energy features of atomic collision dynamics, opening new routes for advanced state-to-state chemistry, for controlling spin exchange in quantum many-body systems for solid-state simulations, or for determination of high-precision molecular potentials.
CRIS-Team Scopus Importer:2023-03-27